Structures and Interactions of Ionic Liquids - Zhang, Suojiang; Wang, Jianji; Lu, Xingmei; Zhou, Qing (Structure and Bonding, 2014)
Kun Dong, Qian Wang, Xingmei Lu, Suojiang Zhang Structures, Bonding and Hydrogen Bonds Jianji Wang, Huiyong Wang Aggregation in System of Ionic Liquids Hui Wang, Gabriela Gurau, Robin D. Rogers Dissolution of Biomass Using Ionic Liquids Yu-Feng Hu, Xiao-Ming Peng Effect of the Structures of Ionic Liquids on Their Physical-Chemical Properties Haoran Li Microstructure study of Ionic liquids by spectroscopy Tiancheng Mu, Buxing Han Structures and Thermodynamic Properties of Ionic Liquids.